Moisture migration analysis of laminated veneer lumber based on low field nuclear magnetic resonance - Yingying Zhu; Jun Yan; Shuilong Lu; Wenqing Ouyang; Shanwen Li; Zhanxiu Chen; Shengbao Feng; Zhong Li (Food Materials Research)
Moisture migration is an important factor affecting the performance and durability of laminated veneer lumber (LVL), a common packaging material. In this paper, we used low-field nuclear magnetic resonance (LF-NMR) and magnetic resonance imaging (MRI) technology to investigate the moisture migration of LVL during water absorption and drying. The results showed that as LVL absorbed water, the signals of both strongly and weakly bound water in the pores increased significantly with time until the samples were fully saturated, and the NMR signals did not change much. The drying process of LVL started with a significant decrease of weakly bound water signals, followed by a gradual decrease of strongly bound water signals until the moisture content in the samples had completely evaporated. MRI was used to observe the water distribution during the water absorption and drying process and found that the visual images were consistent with the quantified NMR spectral results. We also found a linear relationship between the NMR signal and the water mass, and a high correlation between the NMR and weighing results. Our results demonstrated that the combination of LF-NMR relaxation technology and MRI technology is an effective method to analyze the moisture distribution and migration for LVL laminates.